Bioethics to the rescue! A response to Emmerich - Hardman, Douglas (Journal of medical ethics, 2022)
In our article, Where the ethical action is, we argue that medical and ethical modes of thought are not different in kind but merely different aspects of a clinical situation. In response, Emmerich argues that in so doing, we neglect several important features of healthcare and medical education. Although we applaud the spirit of Emmerich’s response, we argue that his critique is an attempt at a general defence of the value of bioethical expertise in clinical practice, rather than a specific critique of our account.